PENGARUH PERILAKU DAN KARISMATIK PENDIDIK TERHADAP MINAT DAN MOTIVASI BELAJAR PESERTA DIDIK - Lediana Lediana; Nofikasyara Dhea; Fortunata Blandina Panamuan (Jurnal Ilmiah Multidisiplin Ilmu, 2024)
This article aims to find out the Influence of Educators' Behavior and Charisma on Students' Motivation and Interest in Learning. The method used is a literature study method, where researchers do not need to go directly into the field to collect data. Through this method, the author seeks to collect, search and evaluate various specific sources that are relevant to the topic discussed. From these sources, the author finds that Educators' Behavior and Charisma are very influential in fostering Students' Motivation and Interest in Learning.   Educators' Behavior and Charisma can affect students' interests and motivation in the learning process. Students' interest and motivation will make it easier to achieve educational goals. The interaction between educators and students is educational, so educators must have integrity. The behavior and charisma of an educator will be observed and assessed by students and will affect the formation of students' personalities. This requires educators to be individuals who can behave well and be exemplary.